2021
DOI: 10.1111/neup.12761
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of titinopathy from a Chinese neuromuscular center

Abstract: Titin, one of the largest proteins in humans, is a major component of muscle sarcomeres. Pathogenic variants in the titin gene (TTN) have been reported to cause a range of skeletal muscle diseases, collectively known as titinopathy. Titinopathy is a heterogeneous group of disabling diseases characterized by muscle weakness. In our study, we aimed to establish the clinicopathologicalgenetic spectrum of titinopathy from a single neuromuscular center. Three patients were diagnosed as having definite titinopathy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The diagnosis of congenital myopathy should be based on a careful review of the clinical features and confirmed by additional investigations, with an exclusionary diagnosis of other myopathies (2,3). Previously, histopathologically oriented classification was widely used for the diagnosis of congenital myopathy, which, although still in use, tends to be replaced by genetic diagnosis in the golden era of modern genetics (4)(5)(6). Accordingly, congenital myopathy can be divided into the following several forms: nemaline myopathy, core myopathy (central core myopathy and multiminicore myopathy), centronuclear myopathy (myotubular myopathy), congenital fiber-type disproportion myopathy, and other congenital myopathies (4).…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of congenital myopathy should be based on a careful review of the clinical features and confirmed by additional investigations, with an exclusionary diagnosis of other myopathies (2,3). Previously, histopathologically oriented classification was widely used for the diagnosis of congenital myopathy, which, although still in use, tends to be replaced by genetic diagnosis in the golden era of modern genetics (4)(5)(6). Accordingly, congenital myopathy can be divided into the following several forms: nemaline myopathy, core myopathy (central core myopathy and multiminicore myopathy), centronuclear myopathy (myotubular myopathy), congenital fiber-type disproportion myopathy, and other congenital myopathies (4).…”
Section: Introductionmentioning
confidence: 99%
“…She has negative genetic testing for SEPT9 gene mutations, and no potentially relevant 4), which has been associated with muscle disease and arrhythmogenic cardiomyopathy. 10 It is not clear if these heterozygous mutations may have played a role in the plexopathy, as non-synonymous heterozygous variations of the TTN gene have been associated with neurological diseases in an autosomal dominant manner. She also had a mutation in MCM3AP gene (MCM3AP; Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Informed consent for participation in our research was obtained from all of the patients, as previously reported in our centre. 9 …”
Section: Methodsmentioning
confidence: 99%